2002
DOI: 10.4049/jimmunol.168.7.3527
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Fibrinogen Modulates Neutrophil Functionality Through the Activation of an Extracellular Signal-Regulated Kinase-Dependent Pathway

Abstract: The integrin family not only mediates the recruitment of polymorphonuclear leukocytes (PMN) to sites of inflammation but also regulates several effector functions by binding to specific ligands. We have recently demonstrated that soluble fibrinogen (sFbg) is able to trigger an activating signal in PMN through an integrin-dependent mechanism. This activation results in degranulation, phagocytosis enhancement, and apoptosis delay. The aim of the present work was to further elucidate the molecular events that fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 59 publications
2
47
2
Order By: Relevance
“…A simple extension of this theory is that in the context of soluble inflammatory mediators, leukocyte engagement of immobilized fibrin(ogen) within inflamed and/or damaged tissues may be an important cue in leukocyte target recognition, ultimately regulating the expression of specialized functions. Consistent with this view, neutrophil engagement of fibrin(ogen) through α M β 2 results in dramatic cellular changes in vitro (15)(16)(17)(18)(40)(41)(42), including calcium mobilization, activation of NF-κB, increased phosphorylation events, degranulation, upregulation of cell surface adhesion molecules, increased migration, and decreased apoptosis. The concept that leukocyte interaction with immobilized fibrin(ogen) is an important event in target recognition has two attractive features.…”
Section: Figuresupporting
confidence: 48%
See 1 more Smart Citation
“…A simple extension of this theory is that in the context of soluble inflammatory mediators, leukocyte engagement of immobilized fibrin(ogen) within inflamed and/or damaged tissues may be an important cue in leukocyte target recognition, ultimately regulating the expression of specialized functions. Consistent with this view, neutrophil engagement of fibrin(ogen) through α M β 2 results in dramatic cellular changes in vitro (15)(16)(17)(18)(40)(41)(42), including calcium mobilization, activation of NF-κB, increased phosphorylation events, degranulation, upregulation of cell surface adhesion molecules, increased migration, and decreased apoptosis. The concept that leukocyte interaction with immobilized fibrin(ogen) is an important event in target recognition has two attractive features.…”
Section: Figuresupporting
confidence: 48%
“…Furthermore, as a protein that is deposited in the form of a provisional fibrin matrix at virtually any site of overt tissue damage, fibrin could serve as a significant nondiffusible cue in regulating leukocyte targeting. Consistent with this general theory, multiple in vitro studies have shown that leukocyte engagement of fibrin(ogen) can profoundly alter leukocyte function, leading to changes in cell migration, phagocytosis, NF-κB-mediated transcription, production of chemokines and cytokines, degranulation, and other processes (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 87%
“…Thus, ERK plays a role in CD11b up-regulation in soluble fibrinogen-activated PMNs but not in IL-1␤-stimulated neutrophils (50,51). Similarly, ERK plays no role in fMLP-stimulated secondary granules exocytosis (52), whereas ERK inhibition decreases the exocytosis of lactoferrin in PACAP-treated 6 / ml) were suspended in HBSS containing 10 M BAPTA/AM for 30 min (intracellular calcium depletion), in calcium-free PBS containing 2 mM EGTA (extracellular calcium depletion), or in HBSS containing 10 M SKF-96365 for 10 min (block in extracellular calcium influx), and then stimulated with 10 M PACAP for 1 min.…”
Section: Discussionmentioning
confidence: 99%
“…To further characterize TREM-1-mediated activation of PMN, we investigated the kinetics of degranulation by monitoring surface up-regulation of CD66b and CD11b as surrogate markers for the release of specific and gelatinase granules, respectively (24,25). Titration experiments of TREM-1-specific mAbs revealed a concentration of 10 g/ml coated on plastic as the optimal dose for inducing degranulation (data not shown).…”
Section: Trem-1 Induces Rapid Degranulationmentioning
confidence: 99%